OPTIMALISASI SUBSIDI PEMERINTAH DALAM MENINGKATKAN KEADILAN AKSES LAYANAN KESEHATAN BAGI MASYARAKAT KURANG MAMPU: TINJAUAN ATAS PROGRAM BPJS KESEHATAN 2025 - Rengga Yudha Santoso; Erick Satria Pratama Wisnu Wardhana (CV. ADIBA AISHA AMIRA, 2025)
The government subsidy programme in BPJS Kesehatan in 2025 has a strategic role in improving equitable access to health services for the poor in Indonesia. Through the Contribution Assistance Recipient (PBI) scheme, the government is trying to remove financial barriers that have been one of the main obstacles for vulnerable groups in accessing health services. However, the effectiveness of these subsidies still faces significant obstacles, such as low accuracy of beneficiary data, administrative complexity, budget constraints, health infrastructure disparities, low public health literacy, cultural barriers, weak inter-agency coordination, and limitations in information technology for data management. These obstacles not only reduce the accuracy of subsidy distribution but also affect the quality of services received by participants. Evaluations indicate that optimising subsidies cannot rely solely on expanding coverage but requires systemic reforms encompassing improved governance, strengthened infrastructure, modernised information systems, and community empowerment through comprehensive education. Adaptive policy approaches, rigorous oversight, and collaboration among stakeholders are key to delivering effective, sustainable, and targeted subsidies. With these strategic steps, it is hoped that the government's goal of achieving social justice in the health sector can be achieved, while ensuring the sustainability of BPJS Kesehatan as one of the pillars of national health insurance.